2010
DOI: 10.1111/j.1469-8137.2010.03414.x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate elicits rapid changes in carbon and nitrogen dynamics in tomato

Abstract: Summary• Evidence is emerging to support the notion that in response to herbivory, plants undergo changes in their primary metabolism and are able to fine-tune the allocation of new and existing resources and temporarily direct them to storage organs.• We hypothesized that simulated herbivory increases the export of resources out of the affected tissues and increases allocation to roots. We used short-lived radioisotopes to study in vivo the dynamics of newly incorporated 11 CO 2 and 13 NH 3 .Methyl jasmonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
126
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 98 publications
(179 reference statements)
10
126
2
Order By: Relevance
“…7,[10][11][12][13] Taken together, our results indicate that sink-source relationships must frequently determine local CHO/N ratios. Many have noted an inverse relationship in entire plants between N availability and the constitutive concentration of CHO-based metabolites, especially polyphenols.…”
Section: Arbon Translocation In Plants Ismentioning
confidence: 95%
See 1 more Smart Citation
“…7,[10][11][12][13] Taken together, our results indicate that sink-source relationships must frequently determine local CHO/N ratios. Many have noted an inverse relationship in entire plants between N availability and the constitutive concentration of CHO-based metabolites, especially polyphenols.…”
Section: Arbon Translocation In Plants Ismentioning
confidence: 95%
“…2-8 We have found that both insect grazing and exogenous jasmonate (JA) trigger increased sink strength, including a 3-fold increase in the import of 13 C-labeled CHOs from orthostichously linked source leaves to sink leaves in poplar saplings. 1,3,4 We recently found that unlike carbon import, nitrogen translocation was not increased by JA treatment in poplar saplings.…”
Section: Arbon Translocation In Plants Ismentioning
confidence: 99%
“…There are many scenarios that could explain the decrease in N, some of which directly involve plant defence, while others are more indirect consequences of herbivory stress. Several possible explanations include: alders released N-containing volatile emissions in response to herbivory (such as methyl anthranilate and indole) [40], methyl jasmonate or the herbivory stress as a whole interfered with or deprioritized nitrogen fixation [41], or N was shunted out of the leaves into other parts of the plant (such as the roots) as a means of resource protection and/or to dissuade further herbivory [42]. The physiological responses resulting in the increased C : N among the herbivory treated trees are quite possibly different among the fertilized versus unfertilized trees (plants growing on N-poor soils often use C-based defences and vice versa) [43].…”
Section: Discussionmentioning
confidence: 99%
“…This was measured as total nitrogen, and may reflect the increase in glucosinolate 392 content when exposed to herbivory. Gomez et al (2010) have shown that nitrogen may be re-393 allocated to other parts of the plant upon herbivory as a strategy to preserve nitrogen for re-394 growth. Whether this was the case for B. vulgaris we cannot determine as roots were not 395 analysed.…”
Section: Interactions Between Albugo and Flea Beetles 335mentioning
confidence: 99%